The Impact of Workload, Work Environment, And Work-Life Balance on Employee Job Satisfaction: A Case Study at The Flea Market in Seminyak, Bali - Dewi, Ni Made Yuli Candra; Saraswati, Ni Putu Ayu Sintya; Purnawati, Ni Luh Gede Putu (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Human resources represent a pivotal component within the economic framework. This is due to the perception of humans as diligent individuals who play a pivotal role within institutions, whether they be organizations or agencies. In accordance with the pivotal function of human resources, job satisfaction is a pivotal factor in determining the extent to which employees have contributed maximally to their workplace. A multitude of factors have been identified as contributors to employee job satisfaction, including workload, work environment, and work-life balance. The objective of this article is to understand how workload, work environment, and work-life balance affect employee job satisfaction at The Flea Market, Seminyak. In this article, the sample size at The Flea Market was 50, employing saturated sampling as the sampling technique, while the analysis technique utilized was multiple linear regression analysis. The findings of the study suggest that the work environment exerts a positive and significant influence on employee job satisfaction. Furthermore, work-life balance demonstrates a positive and significant impact, while workload exhibits a negative and significant effect on employee job satisfaction. In the interest of providing counsel to future researchers, it is recommended that they consider the addition of other independent variables that have the potential to affect employee job satisfaction.